DESKRIPSI KEMAMPUAN KOMU3NIKASI MATEMATIS PESERTA DIDIK PADA PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING KELAS VIII SMPN 34 PADANG - Rita Fajriati (Departemen Matematika, 2022)
This research aims to describe the mathematical communication skills of student who apply the Quantum Teaching model and describe learning activities while the Quantum Teaching model is applied in class VIII SMPN 34 Padang. This type pf research Pre-Experiment with One Shot Case Study design. The subject of this study were students of class VIII SMPN 34 Padang in the academic year 2021/2022 with class VIII.2 as the subject class. The research instrument is a test of mathematical communication skills in the form of essay questions which are analyzed by finding the average class value of the subject then qualified. Based on data analysis, it was found that the average result of the mathematical communication ability test of the students in the subject class was 64,44. After the average is qualified, the mathematical communication skilss of students who learn by applying the Quantum Teaching model are in the good category.Keywords—Mathematical Communication Skills, Pre-Experiment, Quantum Teaching